2016
DOI: 10.15312/eurasianjvetsci.2016215515
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of tetracycline residues in fish caught from surrounding fish farms in Mugla district

Abstract: ÖzAmaç: Su ürünlerindeki ilaç ve metabolitlerinin kalıntı analizleri Ulusal Kalıntı İzleme Planı kapsamında düzenli olarak yapılmaktadır. Fakat Türkiye'de bu kalıntıların sucul ortama etkilerine yönelik araştırmalar sınırlıdır. Bu çalışmada, Muğla bölgesindeki balık çiftliklerinin etrafından avlanan balıklarda tetrasiklin grubu antibiyotiklerin (oksitetrasiklin, tetrasiklin, klortetrasiklin, doksisiklin) kalıntılarının belirlenmesi amaçlandı. Gereç ve Yöntem:Analiz için 70 ayrı çiftlik etrafından toplanan 70 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…They observed that 63.1% of the samples contained the residues of tetracyclines where maximum samples contained residues at a range of 1.43 -91.130 ppb and only one sample (101.40 ppb) exceeds the maximum residue limit of oxytetracycline given by the European Commission. A recent study of Turk and Oguz (2016) observed residues of tetracyclines (oxytetracycline, tetracycline, chlortetracycline, and doxycycline) in 70 fish samples from 70 different fish farms around Muğla province, Turkey. At the end of the analyses, no tetracycline antibiotic residues were found crossing the detection limit.…”
Section: Resultsmentioning
confidence: 99%
“…They observed that 63.1% of the samples contained the residues of tetracyclines where maximum samples contained residues at a range of 1.43 -91.130 ppb and only one sample (101.40 ppb) exceeds the maximum residue limit of oxytetracycline given by the European Commission. A recent study of Turk and Oguz (2016) observed residues of tetracyclines (oxytetracycline, tetracycline, chlortetracycline, and doxycycline) in 70 fish samples from 70 different fish farms around Muğla province, Turkey. At the end of the analyses, no tetracycline antibiotic residues were found crossing the detection limit.…”
Section: Resultsmentioning
confidence: 99%
“…Where they reported at measurable levels 63.1% of the samples were contained with the residues of tetracyclines in which maximum sample contained residues at a range 1.43 -91.130 ppb and only one sample (101.40 ppb) exceeds the maximum residue limit of oxytetracycline set by the European Commission. Turk and Oguz (2016) demonstrated a research to observe the residual effects of tetracyclines (oxytetracycline, tetracycline, chlortetracycline, and doxycycline) in 70 fish samples from 70 various fish farms in Mugla province of Turkey. No tetracycline antibiotic residues were found, cross the detection limit.…”
Section: Oxytetracycline Residues Obtained From Thai Koi Samplesmentioning
confidence: 99%
“…Mahmoudi et al (2014) also reported 8.44±6.03 ppb tetracyclines residues in Oncorhynchus mykiss and the confined tetracyclines residues were lower than the detection limit of present study. Turk and Oguz (2016) found no oxytetracycline in fish samples collected from Muğla province, Turkey. Shim et al (2010) also reported no oxytetracycline residues in some examined fish during their study.…”
mentioning
confidence: 90%